2017
DOI: 10.5194/acp-17-15095-2017
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing energy budget variability at a Sahelian site: a test of NWP model behaviour

Abstract: Abstract. We use observations of surface and top-of-theatmosphere (TOA) broadband radiation fluxes determined from the Atmospheric Radiation Measurement programme mobile facility, the Geostationary Earth Radiation Budget (GERB) and Spinning Enhanced Visible and Infrared Imager (SEVIRI) instruments and a range of meteorological variables at a site in the Sahel to test the ability of the ECMWF Integrated Forecasting System cycle 43r1 to describe energy budget variability. The model has daily average biases of −1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The Sahel is a semiarid region: typically dry and dusty with a high surface albedo in the dry season, contrasting with higher humidity and precipitation in the wet season leading to a large increase in vegetation and decrease in surface albedo (Milton et al, , ). For a more comprehensive overview of radiative processes in the Sahel, we refer the reader to our previous study (Mackie et al, ). The Sahel is also particularly vulnerable to changes in climate, having already suffered from extensive droughts in the past decades (L'Hôte et al, ), and been identified as one of a number of climate change hot spots (Diffenbaugh & Giorgi, ).…”
Section: West African Regionmentioning
confidence: 99%
“…The Sahel is a semiarid region: typically dry and dusty with a high surface albedo in the dry season, contrasting with higher humidity and precipitation in the wet season leading to a large increase in vegetation and decrease in surface albedo (Milton et al, , ). For a more comprehensive overview of radiative processes in the Sahel, we refer the reader to our previous study (Mackie et al, ). The Sahel is also particularly vulnerable to changes in climate, having already suffered from extensive droughts in the past decades (L'Hôte et al, ), and been identified as one of a number of climate change hot spots (Diffenbaugh & Giorgi, ).…”
Section: West African Regionmentioning
confidence: 99%
“…Futyan et al 2005, Slingo et al 2006, Pearson et al 2010, Ansell et al 2014, Banks et al 2014) and to evaluate the representation of these processes in selected numerical weather prediction and climate models (e.g. Allan et al 2007, Greuell et al 2011, Haywood et al 2011, Mackie et al 2017).…”
mentioning
confidence: 99%